2002
DOI: 10.1115/1.1483078
|View full text |Cite
|
Sign up to set email alerts
|

Recent research advances in the dynamic behavior of shells: 1989–2000, Part 2: Homogeneous shells

Abstract: Shell-like structures are used in various engineering applications including civil, aerospace, mechanical, marine, and automotive engineering. This article reviews most of the recent research done in the field of dynamic response of homogeneous shells with special attention to free vibrations. Literature on dynamics of laminated composite shells was reviewed in Part 1 published in the July 2002 issue of AMR. Emphasis is given to the theory being applied (thin, thick, 3D, nonlinear,…), the shell geometries that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(86 citation statements)
references
References 401 publications
0
84
0
2
Order By: Relevance
“…In the abundant literature devoted to nonlinear vibrations of shells (see for example the reviews of Qatu [4], Amabili and Païdoussis [5] and Alhazza and Alhazza [6]), only a few studies propose experimental investigations, as compared to the number of theoretical works available. Moreover, the case of shallow spherical shells is generally reduced to axisymmetric vibrations, whereas asymmetric modes are of prime importance to understand the global dynamics exhibited: 1 they are numerous as compared to the axisymmetric ones, and since nonlinear couplings between any modes are possible [7], an axisymmetric excitation of the structure can lead to asymmetric vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…In the abundant literature devoted to nonlinear vibrations of shells (see for example the reviews of Qatu [4], Amabili and Païdoussis [5] and Alhazza and Alhazza [6]), only a few studies propose experimental investigations, as compared to the number of theoretical works available. Moreover, the case of shallow spherical shells is generally reduced to axisymmetric vibrations, whereas asymmetric modes are of prime importance to understand the global dynamics exhibited: 1 they are numerous as compared to the axisymmetric ones, and since nonlinear couplings between any modes are possible [7], an axisymmetric excitation of the structure can lead to asymmetric vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most published work has been concerned specifically with simple shapes such as cylinders, spheres, cones or, more generally, with shells having small thickness to radius of curvature ratios. Under this assumption, the effect of the curvature on stiffnesses is often negligible [2]. Comprehensive literature reviews on the mechanics of laminated anisotropic shells can be found in recent papers by Qatu [2] and Toorani and Lakis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Under this assumption, the effect of the curvature on stiffnesses is often negligible [2]. Comprehensive literature reviews on the mechanics of laminated anisotropic shells can be found in recent papers by Qatu [2] and Toorani and Lakis [3]. Survey articles often emphasize that shear deformations and rotary inertia effects are generally more important for composites than isotropic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, a shell structure is a three-dimensional structure. In comparison with plates and beams, shells usually exhibit more different dynamic behaviours because they can carry applied various loads effectively by their curvatures [1]. The dynamic characteristic of shells has been studied by many researchers.…”
Section: Introductionmentioning
confidence: 99%